Numerical evaluation of aerosol exhalation through nose treatment. (February 2019) - Calmet, H.; Yamamoto, T.; Eguzkitza, B.; Lehmkuhl, O.; Olivares, E.; Kobayashi, Y.; Tomoda, K.; Houzeaux, G.; Vázquez, M.
Abstract: Aerosol medicine exhalation through the nose (ETN) is one of the most promising and comprehensive treatment methods for Eosinophilic Chronic Rhinosinusitis (ECRS) with asthma. In this work, we performed turbulent Large Eddy Simulations (LES) coupled with a Lagrangian method for particles to model the transport phenomena of aerosol medicine during exhalation. The goal of these simulations is to evaluate the curative effect of ETN. Expiration condition is a critical parameter for the success of ETN, this study proposes to evaluate two different exhalation conditions, exercise and quiet breathing states. As a result of airflow analysis, we observe impinging jet towards the posterior part of nasopharynx, with a subsequent complex swirl and circulation flow in the nasopharynx region. This is the most important zone of turbulence production. As the flow reaches the separation of left and right nasal cavities, the turbulence intensity is greatly reduced. We also observe that particle deposition increases with exercise breathing condition. The most important deposition mechanism is inertial impaction after the turbulent dispersion. Total particle deposition for exercise breathing condition is 5 times more important than for the quiet breathing condition and 7 times more important in the sinuses. Relative important deposition efficiency is observed in sinuses, which represents a significant dose of therapeutic aerosols. In summary, we conclude that ETN is a promising method of drug delivery. Abstract : Highlights: Micro-particle transport and deposition for Exhalation Through the Nose treatment method is proposed. Evaluation of the curative effect of ETN numerically is analyzed during exhalation phase. Air Flow features and particle deposition are described and sinus ventilation is discussed.